Mitigation technique for hamonic using active power filter / Mohd Azri Abd Hakim - Abd Hakim, Mohd Azri (2007)
This paper presents the development of a simulation platform for the study and conception of active power filters. This platform is developed using the MATLAB software as its base, through its environment SIMULINK and other tools, just as PSB (Power System Blockset). The system is composed of AC single phase controllers and a parallel active power filter.